TRANSFORMATION OF TRADITION KUPATAN EID AL-FITR AMONG THE JAVANESE MUSLIM DIASPORA IN MALAYSIA - Ach Hakiki; Dody S Truna; Ilim Abdul Halim; Mochamad Ziaul Haq (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the Eid Kupatan tradition brought by the Javanese Muslim diaspora to Malaysia. The Kupatan tradition is a tradition that existed among Javanese Muslims which was introduced by Sunan Kalijaga during the Demak Kingdom for the Islamization process at that time. The Kupatan tradition is carried out seven days after Eid al-Fitr, in Javanese, ketupat or kupat is interpreted as